2001
DOI: 10.1055/s-2001-16597
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Reconstruction with a Free Vascularized Fibula Graft Associated to Bone Allograft After Resection of Malignant Bone Tumor of Limbs1

Abstract: Over the last twenty years, progress in diagnosis and in adjuvant therapy in the field of malignant bone tumor treatment has allowed for development of limb-saving surgical techniques after oncological excision. In this context, the use of vascularized fibula for transplantation represents an important instrument in the reconstruction of bone, either with or without allografts.Moreover, in pediatric cases, the vascularized transplant of the proximal fibula with its open physis allows for an adequate reconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
78
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 4 publications
2
78
0
5
Order By: Relevance
“…The overall MSTS scores for our patients were comparable to those of massive bone allograft with vascularized fibula ranging between 23 and 27 [4,7,8,20,22,23], whereas one study, in which only pedicled versus free fibula grafts alone were compared, showed poor MSTS scores and overall outcomes for the pedicled graft group [6]. With the numbers we had, we could not show a difference in MSTS scores between the free fibula and the pedicled fibula groups.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The overall MSTS scores for our patients were comparable to those of massive bone allograft with vascularized fibula ranging between 23 and 27 [4,7,8,20,22,23], whereas one study, in which only pedicled versus free fibula grafts alone were compared, showed poor MSTS scores and overall outcomes for the pedicled graft group [6]. With the numbers we had, we could not show a difference in MSTS scores between the free fibula and the pedicled fibula groups.…”
Section: Discussionmentioning
confidence: 69%
“…When used alone, massive bone allografts are associated with complications such as nonunion at the host-allograft junction, allograft fracture, and infection [3,5,17,32]; by contrast, vascularized fibula grafts used alone or supplemental are associated with longer surgical times, risk of donor site morbidity, lengthy times to hypertrophy, and a high frequency of stress fracture [19]. Some studies have suggested that the shortcomings of each technique can be mitigated by using intercalary allografts in conjunction with a vascularized fibula autograft in primary and salvage situations, where immediate mechanical support is provided by the massive bone allograft allowing biologic activity of the vascularized fibula graft to result in hypertrophy and incorporation [7,8]. Ozaki et al [29] modified this technique by using an ipsilateral pedicle vascularized fibular autograft in the allograft shell for reconstruction of the tibia.…”
Section: Introductionmentioning
confidence: 99%
“…There are now a wide range of reconstructive procedures available, which have the potential to maintain limb length while producing an acceptable functional and cosmetic result. These include tumor endoprostheses, either alone [4] or with allografts (composite techniques) [5], osteoarticular allografts [6], intercalary allografts [7][8][9], allografts in arthrodeses [8], clavicula pro-humero procedures [10], skeletal lengthening techniques [11], and autografts using conventional avascularized [12] or free vascularized techniques [5,[13][14][15][16][17]. The decision over which surgical intervention to use depends on tumor-related factors, such as location, size, and soft tissue conditions, as well as patient-related factors, such as age, personal preferences, and cosmetic requirements.…”
Section: Introductionmentioning
confidence: 99%
“…The method has been applied clinically in the treatment of Kienböck disease 29 , talar osteonecrosis 22,30 , and scaphoid nonunion with osteonecrosis 19,31,32 , and in prefabricated bone free flaps [33][34][35] . It also improves the results of necrotic structural allografts 36 and revascularizes massive structural allografts (intramedullary bone autograft) 37 . The potential of surgical angiogenesis to maintain viability of vascularized bone and joint allotransplants with and without short-term immunosuppression has been the focus of our previous research 13,38 .…”
mentioning
confidence: 99%